The influence of immunosuppressive agents on BK virus risk following kidney transplantation, and implications for choice of regimen - Suwelack, Barbara; Sommerer, Claudia (Transplantation reviews, 2012)
The increasing incidence of BK-associated nephropathy following kidney transplantation has prompted an examination of strategies for risk reduction and management through immunosuppression manipulation. Evidence from retrospective and prospective studies suggests that BK viruria and viremia, and the need for BK virus treatment, are higher with tacrolimus than cyclosporine. Combined therapy with tacrolimus and mycophenolic acid may be associated with a particularly higher risk of BK infection, but data are conflicting as to whether mycophenolic acid per se is an independent risk factor. The incidence of BK-related events may be reduced in patients receiving mTOR inhibitors (everolimus or sirolimus) with cyclosporine vs a calcineurin inhibitor with mycophenolic acid. De novo immunosuppression regimens that avoid rabbit antithymocyte globulin and tacrolimus, particularly tacrolimus with mycophenolic acid, may be advantageous, whereas low-exposure cyclosporine with an mTOR inhibitor appears a favorable option. Routine screening for BK infection during the first 2 years posttransplant is recommended to allow preemptive modification of the immunosuppressive regimen. In patients at high risk of BK virus infection, appropriate de novo immunosuppression or very early conversion to an mTOR inhibitor to facilitate reduction or discontinuation of calcineurin inhibitors or antimetabolites should be considered. Extensive further research into optimal avoidance, screening, and treatment strategies is required.
Available online 20 September 2011
Gesehen am 20.06.2018